An Experimental Study on Estimation of the Lateral Earth Pressure Coefficient (K) from Shaft Friction Resistance of Model Piles under Axial Load - Aksoy, Huseyin Suha; Taher, Nichirvan Ramadhan; Ozpolat, Aykut; Gor, Mesut; Edan, Omer Muhammad (Mdpi, 2023)
Estimating a pile shaft's frictional capacity is challenging and has been a controversial subject among researchers. In this study, the shaft friction resistance of non-displacement (pre-installed) model piles under axial load was investigated. Four different model piles were used, including steel, timber, and two composite piles (FRP and PVC filled with concrete). The angle of interface friction (d) between test sand, and pile materials was determined using an interface shear test (IST) at four relative densities. Axial pile load experiments were implemented in a soil tank and piles were embedded into loose to very dense sand. Model pile load tests were performed in such a way that there was no end (point) bearing capacity (only friction was generated), and lateral friction resistance between the pile material and the soil along the pile shaft formed the complete bearing capacity of the model pile. According to experimental results, it was observed that, with increasing sand relative density and surface roughness of the pile material, the shaft friction resistance of the model pile increases. A back-calculation analysis was also performed to find the values of lateral earth pressure coefficient (K) using Burland's (1973) equation with the help of measured shaft friction capacity of the model pile load test. By performing multivariate regression analysis, an equation was obtained between the back-calculated lateral earth pressure coefficient (K) and other parameters. The obtained equation was used to calculate the K values given in other studies in the literature. It was determined that the obtained equation was in good agreement with the data in other studies. This equation can be beneficial in practice and can be advantageous for further study in the future.
Keywords: shaft friction resistance; lateral earth pressure coefficient (K); interface friction angle (& delta;); relative density (Dr); interface shear test (IST)